Knowledge, Attitudes, and Behaviors of Viral Hepatitis Among Recent African Immigrants in the United States: A Community Based Participatory Research Qualitative Study - Mohamed, Essa A.; Giama, Nasra H.; Shaleh, Hassan M.; Kerandi, Linda; Oseini, Abdul M.; Ahmed Mohammed, Hager; Kerandi, Henry; Allotey, Loretta K.; Waaeys, Ibrahim A.; Ali, Hamdi A.; Ali, Hawa M.; Mohamed, Safra A.; et al. (Frontiers in Public Health, 2020)
Background: In the United States, hepatocellular carcinoma is the 9th leading cause of cancer mortality. Hepatocellular carcinoma disproportionately affects individuals of African ancestry with the rates being higher amongst individuals of foreign-born African ancestry. This study explored knowledge, attitudes and behaviors towards viral hepatitis transmission, screening, and vaccination among recent African immigrants in Minnesota and identify ways to improve early detection and screening methods. Methods: A community based participatory research (CBPR) team with minority researchers and community members sought to gain insight on persons of African Ancestry knowledge, attitudes, and behaviors related to viral hepatitis by conducting a qualitative research study. The CBPR team developed a focus group moderator’s guide with semi-structured questions related to transmission, screening and vaccination of viral hepatitis. We conducted seven focus groups using bilingual, bicultural moderators with participants from local Ethiopian, Liberian and Kenyan communities from August 10th, 2014 to October 11th, 2014. Focus groups were audio recorded and transcribed. The CBPR team categorized the data into themes and subthemes with consensus using traditional content analysis. Results: Community partners recruited 63 participants with a majority identifying as male (51%). Participants lacked knowledge of viral hepatitis screening, vaccination and treatment. Participants were aware of some behaviors that increased risk of acquisition of hepatitis. Participants endorsed a strategy of developing and delivering educational materials for African immigrants. Moreover, access to care and cultural awareness were mentioned as pivotal for prevention and treatment of viral hepatitis. Conclusions: Findings from this pilot study provide insight on areas of research focus. Having a research team consisting of members from the community helped to increase trust and foster an understanding of shared community values. Information from this study provides evidence to support the development culturally appropriate strategies to address disparities in viral hepatitis in these communities.